(untitled) (Lakar: Jurnal Arsitektur, 2026)
In contemporary urban contexts, Sport Center buildings are no longer perceived merely as athletic facilities but as architectural representations that shape urban identity. Facade design plays a strategic role in constructing this identity through visual expression, symbolic representation, and technological performance. Previous studies tend to examine facade performance, aesthetic expression, or technological innovation separately, while limited research has comparatively analyzed the integration of these aspects in forming architectural identity. This study aims to analyze the role of facade design in shaping the identity of Sport Center buildings through a comparative approach focusing on three main aspects: form, facade components, and facade technology. A qualitative descriptive method with a comparative analysis framework was applied to three case studies: Gelora Bung Karno Main Stadium (GBK), Jakarta International Stadium (JIS), and Manahan Stadium Surakarta. The findings indicate that architectural identity is formed through the simultaneous integration of visual (form), representative (components), and performative (technology) dimensions. GBK demonstrates a modern–heritage identity based on historical continuity and technological adaptation; JIS represents a futuristic–modern identity characterized by technological dominance and dynamic form; while Manahan reflects a vernacular–modern identity integrating cultural symbolism with adaptive facade systems. This study contributes conceptually by proposing an integrative framework that positions facade design as a multidimensional strategy in shaping the architectural identity of large-scale sports buildings.